Informal Livelihoods and Governance in South Africa The Hustle - Jinnah, Zaheera (Springer Nature, 2022)
This open access book offers a compelling account of everyday life, livelihoods, and governance in post-apartheid South Africa among the urban poor and marginalized, anchored in and through a critique of the concept of informality, or living outside of the state, its laws, services, and protection. Using a case study of the Zama Zama, loosely translated from the isiZulu as 'to hustle, or to strive' and colloquially used to refer to those working as informal artisanal miners on Johannesburg's numerous disused and abandoned gold mines, the book documents an ethnography of this community's everyday lives, struggles, and hopes. It provides an intimate account of a community, its social relations, and its political relationship to the state. The narratives of the Zama Zama are used to raise broader questions about precarity, belonging, and governance in post-apartheid South Africa, and suggest that pervasive informality could risk the country's democratic order.